Representasi Budaya dan Mitos Film KKN di Desa Penari dalam Perspektif Hiperrealitas Jean Baudrillard - Berliana Martasya; Zahwa Alya Putri; Mikha Yunita Puteri; Vieronica Varbi Sununianti; Istiqomah Istiqomah; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the representation of culture and myth in the film "KKN di Desa Penari" (Community Service in Dancer Village) using Jean Baudrillard's hyperreality perspective. This film's phenomenon is not merely entertainment but also demonstrates the blurring of the boundaries between reality and fiction in modern society. The method used is a literature study with a descriptive qualitative approach through a search of scientific sources from 2022–2025. The results show that the representation of culture and myth in film has undergone a transformation into simulacra, a form of representation that no longer reflects reality but instead replaces it. Mystical elements in film tend to be constructed as aesthetic and dramatic visual elements, thus shifting sacred meanings to mere entertainment. Furthermore, the incorporation of magical realism reinforces the experience of hyperreality, making it difficult for viewers to distinguish between fact and fiction. The role of mass media and social media also reinforces this process through the collective production and reproduction of meaning. This study also found a tendency towards stereotypical gender representation, particularly in the depiction of female characters. Thus, the media not only represents reality but also plays an active role in shaping and even replacing social reality in society.